Impact of e-Ticketing on Customer Satisfaction in Kathmandu Valley - Yadav, Ambikesh (Nepalese Journal of Business, 2024)
This study examines the impact of e-ticketing on customer satisfaction in Kathmandu Valley. Customer satisfaction is the dependent variable. The selected independent variables are reliability, responsiveness, assurance, ease of use and data security. The primary source of data is used to assess the opinions of respondents regarding reliability, responsiveness, assurance, ease of use and data security. The study is based on primary data of 127 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of e-ticketing on customer satisfaction in Kathmandu Valley. The study showed that reliability has a positive relationship with customer satisfaction. It implies that increase in reliability leads to increase in customer satisfaction. Likewise, responsiveness has a positive relationship with customer satisfaction. It implies that increase in responsiveness leads to increase in customer satisfaction. Similarly, assurance has a positive relationship with customer satisfaction. It implies that increase in assurance leads to increase in customer satisfaction. Furthermore, ease of use has a positive relationship with customer satisfaction. It implies that increase in ease of use leads to increase in customer satisfaction. Moreover, data security has a positive relationship with customer satisfaction. It implies that increase in data security leads to increase in customer satisfaction.